Efektivitas Relaksasi Autogenik dan Hidrotrapi terhadap Kadar Glukosa Darah pada Pasien Diabetes Melitus Tipe II - Melinda Futri; Ni Made Sumartyawati; Eva Marvia; Rahmani Ramli; Febriati Astut (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
Introduction: Controlling blood sugar levels is the main thing for people with Type II Diabetes Mellitus (DM). The prevalence of Type II DM in Indonesia is increasing from year to year, this is related to the techniques or methods used to control blood sugar. The use of nonpharmacological therapy is important to support blood sugar stability.  Objective: to determine the effectiveness of autogenic relaxation and hydrotherapy on blood glucose levels in Type II Diabetes Mellitus patients.  Method: Quasy Experimental Research with a two group pre post test design, in a population of 82 Type II DM sufferers with a sample of 68 through purposive sampling.  Result: Before being given treatment in the autogenic relaxation group, the highest blood sugar level was hyperglycemia, namely 33 respondents (97.1%) and in the hydrotherapy group, namely 34 respondents (100%), after being given treatment in the autogenic relaxation group, the blood glucose level the majority were normal, namely 19 respondents (55.9%) and in the hydrotherapy group, 21 respondents (61.8%) were normal. The results of the Paired Sample T - Test for the Autogenic group were 0.002 while for hydrotherapy it was 0.000.